METODE TARGHIB DAN TARHIB DALAM PENDIDIKAN MENURUT HADITS RASULULLAH SAW - Ariyani, Dewi; Nursalim, Nursalim (EL TARBAWI, 2016)
Islamic educationâs main objective is to build perfect human beings. To achieve this objective certain methods are required. One of them is the method of targhib and tarhib. In the process of education, targhib and tarhib are viewed as one of effective ways in creating collective awareness of students of what they have done. This paper seeks to understand the method of targhib and tarhib through understanding the method of the Prophet Muhammad as contained in his hadiths (sayings) as can be found in the Shahih Bukhari Collection. The Bukhari collection is one of the most authentic hadiths collections. This will be aided by understanding the socio-historical context and juxtaposed with the Quranic verses and other hadiths as well as other disciplines. The paper argues that the method of targhib and tarhib is a Quranic method that has implication in this world and in the hereafter.